IMPLEMENTASI MODEL PEMBELAJARAN ARIAS UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR IPS - Eka Nofri Ari Yanto (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2016)
Implementation of learning model arias in learning activities to build a sense of confidence or thurst in students. Learning activities are relevant to student that trying to attract and maintain students interest. Then, the evaluation and develop a sense of pride in students by providing reinforcement. Arias general learning model can improve students motivation. The problems  encountered during the study was some students confused with the implementation of learning. There were students who are not active and not all student motivated by bringing in speakers. The strengthen was the learning become fun, students become active, spirit, motivation and learning achievement increased.Keywords: Aries Learning Models, learning Motivation, Learning Achievement.